Upaya Peningkatan Partisapasi Belajar IPS Melalui Case Method Pada Materi Fitur Geografis Kaitanya Dengan Fenomena Geosfer Di Kelas VII.1 SMP Negeri 3 Lembah Gumanti - Dahliar Dahliar (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Learning in the implementation of the independent curriculum demands educators to focus on competency development and the quality of learning, flexibility in time and learning materials, as well as character reinforcement. Action Research in this case aims to enhance learning participation using the case method in Social Studies lessons at SMP Negeri 3 Lembah Gumanti. The subjects of this research are 33 students from Class VII.1 at SMP Negeri 3 Lembah Gumanti. The research is designed in the form of Classroom Action Research (PTK), which consists of planning, implementation, observation, and reflection. The research itself is conducted in 2 cycles. Data is collected through observation sheets and assisted by an observer, then analyzed descriptively. There is an improvement in student learning participation through the implementation of the case method in Social Studies lessons in Class VII.1 at SMP Negeri 3 Lembah Gumanti. The improvement is evident from the increased percentage of learning participation in the first cycle, which is 55.55%, and a significant increase in the second cycle, which is 83.33%. The use of the case method enhances learning participation, including motivation in completing tasks, the courage to express opinions and respect others' opinions in learning, as well as problem-solving. Such conditions are part of the goals of learning in the implementation of the independent curriculum, which emphasize active and participatory learning.